2021
DOI: 10.1016/j.jbc.2021.101012
|View full text |Cite
|
Sign up to set email alerts
|

Phenothiazines alter plasma membrane properties and sensitize cancer cells to injury by inhibiting annexin-mediated repair

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 73 publications
0
36
0
Order By: Relevance
“…To combat these stresses, cells of all sizes have developed robust wound repair mechanisms to alleviate the chances of infection or death [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Cell wound repair is highly conserved and a variety of model organisms and systems have been developed to study this process, including the Drosophila syncytial embryo [ 9 ], Xenopus oocytes [ 10 , 11 ], Dictyostelium [ 12 ], sea urchin eggs [ 13 ], C. elegans [ 14 ], and tissue culture cells [ 15 , 16 ]. These have proven to be excellent and complementary systems for studying this dynamic cell biological process and for identifying the molecular players/pathways involved.…”
Section: Introductionmentioning
confidence: 99%
“…To combat these stresses, cells of all sizes have developed robust wound repair mechanisms to alleviate the chances of infection or death [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Cell wound repair is highly conserved and a variety of model organisms and systems have been developed to study this process, including the Drosophila syncytial embryo [ 9 ], Xenopus oocytes [ 10 , 11 ], Dictyostelium [ 12 ], sea urchin eggs [ 13 ], C. elegans [ 14 ], and tissue culture cells [ 15 , 16 ]. These have proven to be excellent and complementary systems for studying this dynamic cell biological process and for identifying the molecular players/pathways involved.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative to antibody therapy would be to use small molecule inhibitors or peptides. Drugs used to treat psychiatric and allergic conditions, such as trifluoperazine, have been reported to inhibit annexin-mediated membrane repair 32 , and a synthetic cell-penetrating peptide that interacts with ANXA2 has been shown to reduce metastasis to murine lungs 33 . Major compressive and shearing forces are encountered during invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that phenothiazine derivatives, especially trifluoperazine (TFP), are able to inhibit the repair function of ANXA proteins at the cell membrane. TFP delays the accumulation of ANXA2-GFP at the damaged plasma membrane, inhibits ANXA-mediated membrane curvature, affects the membrane-forming ability of ANXA and, to some extent, impairs ANXA proteins from binding to membrane patches (Table 3) (Heitmann et al, 2021). Not only inhibitors, but also their functions need deeper investigation.…”
Section: The Inhibitors Of the Anxa Protein Familymentioning
confidence: 99%